The Labour Movement in Britain from Thatcher to Blair With a Foreword by Jim Mortimer- Extended and Updated Edition - Barlow, Keith; Barlow, Keith (Peter Lang, 1997)
British economic and industrial policy since 1979 is examined using a wide range of sources. Was this really (S0(Bnew(S1(B, revival of earlier approaches or a rigorous extension of the IMF-imposed policies on the 1974-79 Labour Government? The question is asked: Was the creation of a large pool of unemployed labour necessary for reshaping the economy or was the aim to secure fundamental changes in the relations between capital and organised labour? Due to setbacks suffered by trade unions in the 1980s with factory closures and major job losses, the author questions Labour$1 (Bs motives in softening any meaningful opposition to the Conservatives, supporting ERM in 1990, reducing the role of trade unions in the Party itself and retaining key policies of the Thatcher era especially its trade union laws.s